Renewing old acquaintances: the conflation of critical and translational paths in the Anglo-American reception of Merce Rodoreda, Esther Tusquets, and Rosa Montero - Miguélez-Carballeira, Helena (The University of Edinburgh, 2005)
The thesis looks at the patterns, tendencies, and tensions that characterise the AngloAmerican critical reception of the three peninsular woman authors Merce Rodoreda, Esther Tusquets, and Rosa Montero, generally assigned a representative role as feminist writers in the field of gender-centred Hispanism. The study begins with the recognition that there has been an increase in the level of awareness as to certain recurrent mechanisms of academic Hispanism in America, as is proved by the recent burgeoning of studies with an avowed metacritical slant. My analysis partakes in this trend but integrates also translational analysis, with a view to showing the validity of translated texts as critical artefacts, informed by similar operations and leanings. Ultimately, my aim is to shed light on the often downplayed complexities characterising ideologically inflected instances of cultural reception and diffusion, of which the Anglo-American critical response to women-authored, contemporary narrative in Spain is a case in point. In the thesis I try to make evident two aspects of this diffusion. First, that critical enquiry around these authors is fuelled by an ever-present negotiation around the true feminist valence of their work. As a result, questions of wishful anticipation on the part of the critics or the much-referred clash between Spanish authors and Anglo-American scholars as regards their attitude towards the feminist label, have a times precluded less jaundiced readings. Second, that it was nevertheless the critics' emphasis on the original works' feminist worth that initially brought them to the fore, nourished scholarly dialogue on them for more than two decades now, and yielded the English translations of some of their novels. The thesis attempts to show, by contrast, that this last stage of the process of dissemination (that is, the translated texts) is at variance with the claims adduced in the secondary literature, despite the claims of 'concertedness' expounded in paratextual material and the editorial milieus that supported their publication. Specifically, the feminist value underscored by critics is substantially neutralised by dint of a variety of translational strategies that this study aims to disclose. By combining metacritical and translational forms of analysis, the study of these particular paths of critical reception is thus rendered more complex and aims to problematise the apparent transparency implicit in the international movement of cultural goods.
Keywords: Hispanism; feminist; translational analysis